Métodos em nutrição de ruminantes: uso de índices fecais para estimar consumo e estimativa da síntese proteica microbiana ruminal - Oliveira, Lisandre de (2009)
This study was carried out to evaluate methods in ruminant nutrition: use of fecal index to estimate intake and use of purine or purine derivatives to estimate rumen microbial protein synthesis. Data from three digestibility trials conducted with castrated male lambs fed ryegrass (Lolium multiflorum, Lam) or Cynodon (Cynodon dactylon var dactylon) at different levels of intake were compiled. Intake data were related to faecal excretion of different chemical compounds through regression analysis. Significant regressions with high R2 were used to calculate estimated intake values, which were compared to observed values by paired t test. Organic matter (OM) intake (g/day) had significant (P<0.01) relation to faecal excretion (g/day) of N and/or acid detergent fiber (ADF) in ryegrass trial (R2 varied from 0.69 to 0.85) while N, ADF and neutral detergent fiber (NDF) had significant (P<0.01) relation to OM intake in Cynodon trials (R2 varied from 0.51 to 0.56). It is concluded that faecal excretion of N and/or ADF had high potential to estimate intake by grazing animals. Rumen microbial protein synthesis estimated either by duodenal purines or urine purines derivatives was different (P<0.01). Moreover, these estimates were highly affected by purines:microbial N proportion used in calculations.